2022
DOI: 10.1088/1742-6596/2356/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Dust on the Surface of Photovoltaic Panels in Low Latitude and High Altitude Plateau Areas

Abstract: Fossil energy consumption and climate crisis have witnessed an allure towards harnessing solar energy. Nevertheless, dust weather leads to the inevitable power output deterioration of the photovoltaic (PV) station. Dust-PV connection studies have been widely concerned in the semi-arid and desert regions at low latitudes and altitudes. However, dust’s properties on PV panels in low latitude and high altitude plateau areas in Sichuan province of China remain relatively in the dark. Here, the chemical and physica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Brahim Aïssa and his team presented various articles to demonstrate that wind direction and tilt angle could potentially be beneficial in reducing pollution 20 . Changquan suggested that differentiated cleaning strategies, including tilting to target wind direction, can effectively reduce dust 21 . Against the background that a majority of new installations in deserts are using one‐axis trackers, storing the modules vertically or upside down during the night is considered as a widely applicable solution to reduce soiling up to 50% at acceptable costs 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Brahim Aïssa and his team presented various articles to demonstrate that wind direction and tilt angle could potentially be beneficial in reducing pollution 20 . Changquan suggested that differentiated cleaning strategies, including tilting to target wind direction, can effectively reduce dust 21 . Against the background that a majority of new installations in deserts are using one‐axis trackers, storing the modules vertically or upside down during the night is considered as a widely applicable solution to reduce soiling up to 50% at acceptable costs 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…20 Changquan suggested that differentiated cleaning strategies, including tilting to target wind direction, can effectively reduce dust. 21 Against the background that a majority of new installations in deserts are using one-axis trackers, storing the modules vertically or upside down during the night is considered as a widely applicable solution to reduce soiling up to 50% at acceptable costs. 9,10 Adoptive tracking techniques have been investigated by Ricardo to improve PV performance and reduce soiling.…”
mentioning
confidence: 99%
“…Innovative passive and advanced cleaning technologies offer efficient solutions, while interdisciplinary approaches involving physics, impact analysis, machine learning, and thermal conductive coatings can optimise solarwind hybrid systems, ensuring sustained power generation and reduced loss due to dust deposition. The research in [15] analyses dust effects on solar PV stations in Sichuan's Ganzi region. SiO 2 and CaCO 3 are identified as primary dust phases, with unique trace elements like Rb, Y, and Sr.…”
Section: Introductionmentioning
confidence: 99%